Alih Kode Dan Campur Kode Dalam Proses Pembelajaran Di SD Sekolah Dasar Swasta Gereja Kristen Protestan Simalungun: (Kajian sosiolinguistik) - Tresia Indah Sari Purba; Sonira Agita Sinaga; Regita Sari Situmorang; Eka Putri Saptari Wulan (Jurnal Mahasiswa Kreatif, 2024)
Code switching and code mixing often occur in different conversations in society, code switching and code mixing can occur at all levels of society, a person's social status cannot prevent code switching or code mixing from occurring, this is often called multilingualism. This qualitative descriptive research was conducted in the fourth grade learning process at the Simalungun Protestant Christian Church Elementary School with the aims of 1) describing the types of code switching applied by teachers in the learning process; 2) describe the types of code mixing carried out by teachers in the learning process; 3) describe the factors that cause teachers and students to exchange codes; and 4) describe the factors that cause teachers and students to mix code.The methods used are observation and interviews. The results of this research indicate that in the fourth grade Simalungun Protestant Christian Church Elementary School, code switching occurred in the form of internal code switching. Internal code changes include code changes from Indonesia to Simalungun and Simalungun code changes to Indonesia. The form of coding codes in the Simalungun Regency Christian Church Elementary School class IV consists of additional word codes, phrase codes and sentence codes. The factors causing code mixing are (1) explaining something, (2) creating familiarity, and (3) situations and conditions